Improved Average Figure‐of‐Merit of High‐Efficiency Nonfullerene Solar Cells via Minor Combinatory Side Chain Approach. Issue 6 (2nd April 2020) - Yuan, Dong; Pan, Feilong; Zhang, Lianjie; Jiang, Haiying; Chen, Mingjun; Tang, Wei; Qin, Guoming; Cao, Yong; Chen, Junwu
Abstract : The cost‐effectiveness of polymer solar cells is a very important concern for future applications. In this work, a new combinatory side chain integrating siloxane terminal and alkoxy group is developed, and three polymers, PQSi05, PQSi10, and PQSi25, with 5%, 10%, and 25% contents of the siloxane‐terminated alkoxy side chain, respectively, are successfully synthesized. As the content of the combinatory side chain increases, the surface energy of the corresponding polymer film decreases, showing tunable miscibility in blend films with nonfullerene acceptor IT‐4F. A maximum power conversion efficiency (PCE) of 13.56% is achieved in the PQSi05:IT‐4F‐based device. The minor (5%) combinatory side chain approach retains a low synthetic complexity (SC) of 16.58% for PQSi05. Due to the improved device performance, a low figure‐of‐merit (FOM) of 1.22 is obtained for the PQSi05:IT‐4F blend. Furthermore, the contribution of the IT‐4F acceptor is considered for a comprehensive analysis, yielding an average SC (ASC) of 39.31% and an average FOM (AFOM) of 2.90. After statistical analyses and calculations, the PQSi05:IT‐4F is the best cost‐effective active layer to date. It is revealed that the introduction of the minor combinatory side chain is a promising strategy to develop high‐performing and cost‐effective polymer donors. Abstract : With the minor new combinatory side chain, the resulting polymer PQSi05 maintains low synthetic complexity and its related blend system achieves optimal average synthetic complexity and average figure‐of‐merit.